Analisis Kapasitas Fiskal Dan PengaruhnyaTerhadap Anggaran Belanja Modal Pada Pemerintah Daerah Di Sumatera - Liza Fiona; Taufeni Taufik; Vince Ratnawati (Jurnal Ekonomi, 2016)
This study aims to determine the effect of Local Own Revenue, Revenue Sharing, General Allocation Funds, Other Local Revenues, and Personnel Expenditure affect the Capital Expenditure Budget District / City Government on the island of Sumatera. The population in this study is the district/city governments in Sumatra from 2009 to 2013. By using the purposive sampling method, of 151 regencies / cities in Sumatra obtained a sample of 122 districts/cities. This research is a quantitative research using secondary data. Testing the hypothesis in this study using multiple linear regression with t test, and the coefficient of determination. The results showed that the Local Own Revenue, Revenue Sharing, General Allocation Funds significant affect Budget Capital Expenditure, Other Local Revenue no effect on the Budget Capital Expenditure, while personnel expenditure has a significant effect but with a negative direction.